Forests and poverty alleviation (Food and Agriculture Organization of the United Nations, 2003)
It focuses on the role of forests, particularly natural ones, in poverty alleviation in developing countries. While some attention is given to the potential of planted forests and agroforestry to alleviate poverty, space constraints allow only a passing reference to trees outside forests. Thus, while not attempting to provide an extensive analysis of the topic, the chapter defines forest-based poverty alleviation, examines the potential of forests in this regard, notes obstacles to progress, identifies conditions that may strengthen the role of forests in alleviating poverty, and proposes several strategies to improve the contributions of the forest sector. Forests can be vital safety nets, helping rural people to avoid, mitigate or rise out of poverty. This function is unknown to many policy-makers and planners because it is not well understood or explained. One reason is that the contribution of forests to poor households is largely unrecorded in national statistics, as most of it is for subsistence or for trade on local markets. In addition, most wealth from timber goes to better-off segments of society, while some aspects of the access to and processing of timber resources actually inhibit their potential to assist marginalized people. Despite these obstacles, the contribution of forests to poverty alleviation can be increased, provided that decision-makers recognize and act on this potential.